Study Habits of University Students - Burján-Mosoni, Boglárka; Vámosiné Varga, Adrienn (International Journal of Engineering and Management Sciences, 2024)
What kind of electronically available content can students prefer? We conducted a questionnaire survey in which we asked about the study habits of university students: where, how, with whom, when, how much, where do they study? Do they use problem-solving software? We need to find out about it, since learning habits and strategies have changed significantly in recent years. Taking into account the answers to the questionnaire, we draw attention to some activities that improve the quality of education.